2023
DOI: 10.1021/acs.macromol.3c01366
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Dynamics, and Rheology of Vitrimers

Jianshe Xia,
Julia Ann Kalow,
Monica Olvera de la Cruz

Abstract: Vitrimers are associative covalent adaptable networks that undergo reversible bond-exchange reactions while maintaining a fixed cross-linking density with changing temperature. To date, experimental studies that rely on macroscopic rheology have not been able to reveal topological changes and microscopic dynamics in these materials. Here, coarse-grained molecular dynamics simulations combined with a Monte Carlo method are implemented to investigate the topological structural changes, microscopic dynamics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 67 publications
1
21
1
Order By: Relevance
“…We note that a very recent simulation study at a single cross-link density found such a bending-up behavior of the bond exchange time . There, the strong upturn behavior was interpreted as beginning at the so-called topological freezing transition temperature, T v .…”
Section: Theoretical and Experimental Backgroundmentioning
confidence: 61%
See 2 more Smart Citations
“…We note that a very recent simulation study at a single cross-link density found such a bending-up behavior of the bond exchange time . There, the strong upturn behavior was interpreted as beginning at the so-called topological freezing transition temperature, T v .…”
Section: Theoretical and Experimental Backgroundmentioning
confidence: 61%
“…The prediction of even stronger upturns at lower temperatures than probed experimentally is a target for future laboratory studies. As discussed above, a recent simulation also found a crossover of the exchange time from an Arrhenius law regime to the bending up regime which was attributed to topological freezing of bond exchange. This interpretation is different from our conclusion here that the crossover is attributed to the importance of activated glassy segmental relaxation physics ( t p τ α,K ) on bond exchange.…”
Section: Experimental Applicationmentioning
confidence: 73%
See 1 more Smart Citation
“…We hypothesize that the molecular picture of our CANs and their stress relaxation could be modeled by sticky reptation theory, initially described by Leibler, Rubinstein, and Colby . Although sticky reptation theory has been commonly employed to explain the behavior of entangled multisticker polymers, it has seldom been discussed in the context of associative CANs (vitrimers) or dissociative CANs. , Discussions of sticky theories in the context of CANs have largely been limited to unentangled CANs modeled by sticky Rouse theory. In sticky reptation theory, entangled polymers containing reversible junctions (known as “stickers”), such as hydrogen bonds, metal–ligand interactions, or dynamic covalent cross-links, may exhibit an additional relaxation process dictated by the slow dissociation of stickers and their subsequent diffusion to find other sticker partners. This additional relaxation process occurs following an initial relaxation attributed to the Rouse motions of sol chains and reptation of some entanglements (at a length scale below the size of network strands) .…”
Section: Resultsmentioning
confidence: 99%
“…The relaxation dynamics are known to be dominated by the bond exchange rate in a given system. [32][33][34] In the present system, the dynamics should be determined by the frequency of interdomain bond exchange. Thus, if the bond exchange is trapped in the matrix, the relaxation rate is naturally slowed.…”
Section: Discussionmentioning
confidence: 99%